The cane or marine toad, Rhinella marina (Anura, Bufonidae): two genetically and morphologically distinct species - Acevedo, Aldemar A.; Lampo, Margarita; Cipriani, Roberto (Zootaxa, 2016)
Rhinella marina is a Neotropical toad that has been introduced widely worldwide. Its toxic effects to frog-eating predators threaten the native and domestic fauna of some regions where it has been introduced. Despite previous studies suggesting two genetically distinct cryptic species within R. marina, one east and one west of the Andes, its taxonomic status remained unresolved due to the absence of morphological complementary evidence. For the first time, data from two mitochondrial genes (ND3 and CR) and 23 morphometric landmarks are combined to evaluate the taxonomic status of this species. Our results support the hypothesis of two separate evolutionary lineages within R. marina and demonstrate that these lineages have significantly diverged in skull shape. We identified two distinct morphotypes, one eastern and one Andean western, with no overlapping morphospaces. The geographic pattern of genetic variation was consistent with a stable structured population with no evidence of recent demographic or geographic expansions. The concordance between the observed geographic patterns in morphometric and genic traits calls for the recognition of two species under R. marina name.